Athenian settlements of the fourth century B.C. - Cargill, Jack. (Mnemosyne, Supplements, 1995)
This work surveys all available evidence on Athenian settlements and settlers of the fourth century B.C., calling several conventional interpretations about them into question, through a rigorous preference for evidence over speculation. Three chapters trace a chronology of events relating to the settlements, examine their personnel collectively, statistically, and individually, and discuss evidence for their political, economic, and religious institutions. Long appendixes establish improved texts of numerous inscriptions relevant to the topic and provide several kinds of data on more than 1000 definite, probable, or possible settlers.